Design and develop a flexible earpiece plug to shield out noise - Su, Liwei (2015)
Despite the efforts from organizations and the availability of hearing protectors, noise induced injury still remains the most common type of work related injury in the manufacturing sector. Most users choose not to wear hearing protectors due to the discomfort level and hygiene concern. Therefore, the purpose of the project is to design and develop a flexible hearing protector to shield out ambient noise without compromising comfort and hygiene. This project started with review on the current hearing protector devices and steps to design and develop a new hearing protector. Functional analysis and morphological chart were applied to generate new concept designs. Decision matrix was then used to choose the best concept design for functional prototyping and product fabrication. The fabricated device was tested on the silicone replicated ear mounted onto the experiment set-up. 4 configurations of set-ups namely “fully opened” fully closed”, “earpiece off” and “earpiece on” were tested to find the decibel level at each set-up. The results show that the maximum possible decibel reduction in this experiment was 5dB and the fabricated earpiece was able to reduce by about 4dB. The differences in the decibel level might due to noises entering from the small gaps around the ear bud and ear canal. Thus, it can be improved by replacing the ear bud with a compressible material to create a tighter seal and close up the gaps when pressed on the ear canal.